Exploration of Factors Affecting Tax Avoidance Practices: The Case of Healthcare Companies on the Indonesia Stock Exchange 2018-2022 - Merry Hanif Rahma; Nurafni Eltivia; Nur Indah Riwajanti (Komunitas Dosen Indonesia, 2024)
This research examines the impact of leverage, liquidity, sales growth, and firm size on tax avoidance, both individually and collectively, within the healthcare sector companies listed on the IDX from 2018 to 2022. The research employs a quantitative approach to purposive sampling to select qualifying companies based on predetermined criteria. The analysis involves multiple linear regression, determination coefficient calculation, and hypothesis testing through t-tests and F-tests. The findings indicate that firm size partially influences tax avoidance among healthcare sector companies on the IDX from 2018 to 2022. Meanwhile, leverage, liquidity, and sales growth do not individually affect tax avoidance during the same period. Simultaneously, the study reveals a significant combined impact of tax avoidance, leverage, liquidity, sales growth, and firm size on healthcare sector companies listed on the IDX from 2018 to 2022. The researchers recommend exploring new variables, broadening the sample to include diverse sectors, conducting cross-country comparisons, and considering alternative proxies like ETR or GAAP ETR for a more comprehensive understanding of tax avoidance.